Evaluation of the Death Cases due to Electric Current Being Performed Autopsies Between 2007 and 2014 Years in Diyarbakır - Mustafa Korkmaz; Cem Uysal (Adli Tıp Bülteni, 2021)

(untitled)
Objective:Electrical injuries are an important cause of mortality and morbidity and they may be prevented by simple precautions in general. The present study aimed to review the death cases due to electric current in Diyarbakır region between 2007 and 2014.Methods:In this study, 6341 forensic death reports were analyzed retrospectively. The study included 239 (3.77%) deceased individuals died because of electrical injury. Age, gender, origin of death, the crime scene, location of electrical entrance and exit points on the body were reviewed.Results:The cases included 147 (61.5%) males and 92 (38.5%) females, and the average age was 23.15+17.1 years [mimum (min): 1, maximum (max): 78]. All deaths due to electric current were accidental. Most of deaths occurred during summer season. The most common contact site was the upper extremity, which was detected in 112 (46.9%) cases. There were 34 cases (14.2%) without any external lesions due to electric current. Seventy-six (46.6%) cases died due to home accidents. The most significant findings of our study were that 114 (47.7%) cases were between 0 and 18 years of age and immersion water heaters were the cause of the incident in 33 (28.9%) cases.Conclusion:Among all forensic death cases of the current study, death rate due to electric shock was found to be higher compared to previous studies. Rate of pediatric deaths due to electric shock was found to be higher in the present study. Therefore, children should be educated to avoid playing with household electric appliances. Furthermore, infrastructure problems should be resolved and safety measures should be taken to prevent such accidents.